Veno-arterial extracorporeal membrane oxygenation as a bridge to recovery in acute aluminium phosphide poisoning: A case report - Arvind Kumar; Jai Prakash; Gaurav Arya; Yadav, Anand Kumar; Dhankar, Aman (Asian Journal of Medical Sciences, 2022)
Aluminium phosphide (AlP) is a common fumigant used for controlling rodents and pests in grain storage facilities. Its consumption is reported in accidental or suicidal cases carrying high mortality. In the present case, a young male was reported with ingestion of AlP with severe lactic acidosis and systolic dysfunction. The patient was managed with extracorporeal membrane oxygenation. In reserved cases, ECMO can be instituted taking in view of risk and complications.